(untitled) (Bangladesh Journal of Medical Science, 2018)
Objectives: To assess oxidative damage and lipid profile levels in Type 2 diabetes mellitus patients with or without tobacco chewing habit. Methods: Total of 141 newly diagnosed Type 2 diabetes mellitus patients with tobacco chewing habit from past >18 years were included, 136 Type 2diabetes mellitus without any tobacco chewing habit, 140 normal healthy subjects without any tobacco chewing habit were included in the study. Blood sample was collected after 8-12 hours fasting from each subject to estimate glucose and cholesterol. The plasma was used for estimation of total antioxidant (TAA) activity, Vitamin C and thiobarbituric acid reacting substances (TBARS) by standard methods. Statistical analysis was done with SPSS version 16. Results: The glucose, cholesterol and TBARS levels were found to be increased significantly (p<0.001) in diabetic patients with tobacco chewing habit, as well as TAA, Vitamin C levels decreased significantly (p<0.001) when compared with healthy individuals. Conclusion: We observed increased oxidative stress and declined levels of antioxidants in newly diagnosed type 2 diabetes patients with tobacco chewing habit. It is known that hyperglycemia induces oxidative stress and further facilitate the progression of diabetic complications. Bangladesh Journal of Medical Science Vol.18(1) 2019 p.78-82